(untitled) (Research, Society and Development, 2022)
In the last decades, there have been great developments in the area of technology of construction materials and with that, concretes were obtained that reach high resistance and provide an interesting durability due to the use of additives and a reduced water/cement ratio. The implementation of technological control processes for concrete is of great importance to obtain the expected quality of the material requested in the project, aiming at an increasingly competitive market. In view of this, it is necessary to know the most economical solutions and with the best performance in the area of civil construction. In this sense, this comparative study initially evaluates the aggregates used, performing characterization tests. Then, a trait was chosen based on customer demand and the need to reduce the consumption of cement used in the concrete plant where the present study was carried out. With this, 18 traces were rotated, using three brands of polyfunctional water-reducing additives and six brands or types of cement, with 08 specimens being molded for each trace rotated and their compressive strength analyzed at ages 1, 3, 7 and 28 days. Then, the additive content to be used in the traces was recommended by the manufacturers, staying at 0.8% in additive A, 0.85% in additive B and 0.7% in additive C. The results achieved contributed to a greater assimilation as to the interference of additives in different cement samples in high strength concrete mixes, both in the first hours and during the first ages.